Analisis fungsi ekologis mangrove sebagai pencegahan pencemaran air tanah dangkal akibat intrusi air laut - Mia Fitri Aurilia; Deni Rahman Saputra (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2020)
Jangkaran Village that located in a coastal area, has the potential for sea-water intrusion to occur through groundwater. Mangroves have major benefits of preventing sea water intrusion in coastal and estuary areas. This study aimed to determine the ecological function of mangroves in the prevention of sea water intrusion and the relationship of groundwater quality around coastal areas with the presence of mangroves. The study was conducted around Jangkaran and Karanganyar Village. The methods used were survey and mapping, groundwater sampling, and laboratory tests. Analysis was carried out based on literature and laboratory results. Laboratory test parameters used were pH, turbidity, TDS, EC and salinity. The results showed the analyzed water quality parameters were not affected by sea water intrusion due to activity in the southern sea of ​​Java. Test parameters showed results below the saltwater threshold. Mangrove cover can be one of the factors causing obstruction of sea water intrusion into community wells. However, the physical quality of the water was inadequate and the residents dug wells were not used for domestic needs, only for urgent purposes. The poor physical quality of water was indicated to occur due to the large number of pond activities around the study area.